FORMATION OF ORTHOGRAPHIC SKILLS AT THE LESSON OF UKRAINIAN LANGUAGE IN PRIMARY SCHOOL - Khoma, Olga M. (Educological discourse, 2015)
The article reviews the main approaches to the study of spelling rules. It includes requirements of the new State standard of primary education on the subject «Language and Literature» and the curriculum of Ukrainian language on creating a culture of written language. It analyzes principles of orthographic and specificity study indicates some spelling rules. The author develops methodology of doing separate exercises such as: writing-off, training dictations.